1985
DOI: 10.1002/ana.410170314
|View full text |Cite
|
Sign up to set email alerts
|

The role of plasma lipids in carotid bifurcation atherosclerosis

Abstract: The severity of coronary artery atherosclerosis correlates with increased plasma concentrations of total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), and triglycerides and with decreased plasma concentrations of high-density lipoprotein cholesterol (HDL-C). The role of plasma lipoproteins in the pathogenesis of cerebral atherosclerosis, however, is less clear. Several investigators report that lipoprotein abnormalities correlate inversely with the incidence of cerebral infarction. We analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1

Year Published

1987
1987
2003
2003

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(16 citation statements)
references
References 17 publications
1
14
1
Order By: Relevance
“…In some studies, LDL cholesterol concentration has paradoxically shown an inverse relation to events. 3 * We found HDL cholesterol concentration to be independently and inversely related to the extent of carotid atherosclerosis in multivariate analysis, whereas plasma concentrations of triglyceride, total cholesterol, and LDL cholesterol, in agreement with a prior report, 5 were not significant and did not remain in the equation. Use of the HDL:total cholesterol or HDL: LDL ratios did not improve our ability to explain variability in the extent of extracranial atherosclerosis.…”
Section: O -21supporting
confidence: 89%
“…In some studies, LDL cholesterol concentration has paradoxically shown an inverse relation to events. 3 * We found HDL cholesterol concentration to be independently and inversely related to the extent of carotid atherosclerosis in multivariate analysis, whereas plasma concentrations of triglyceride, total cholesterol, and LDL cholesterol, in agreement with a prior report, 5 were not significant and did not remain in the equation. Use of the HDL:total cholesterol or HDL: LDL ratios did not improve our ability to explain variability in the extent of extracranial atherosclerosis.…”
Section: O -21supporting
confidence: 89%
“…20,21 IMT was found to correlate with LDL-C and triglyceride and to correlate inversely with HDL-C. 13 In the fasting state, LDL-C, but not HDL-C and plasma triglycerides, was related to IMT in 50-year-old white men. 22 Lp(a) was also suggested as a risk factor for carotid atherosclerosis.…”
Section: Potential Role Of Lipoprotein Metabolism In Carotid Atheroscmentioning
confidence: 96%
“…15 ' 16 One study 15 found that the average stenosis of the two internal carotid arteries was correlated with age, total cholesterol concentration, the high density lipoprotein cholesterol: total cholesterol ratio, history of smoking, and hypertension; however, that study assessed the variables individually, with no adjustment for the confounding effects of any variables other than age. The Italian Multicenter Study 16 included only patients with symptomatic cerebrovascular disease, and the authors found that history of cigarette smoking, age, and cholesterol level were related to the presence of extracranial CAS; however, only cigarette smoking was related to the severity of extracranial CAS.…”
Section: Discussionmentioning
confidence: 99%